Taller de alimentación, nutrición, dietética y su incidencia en el desarrollo cognitivo en el aula taller en la carrera de educación parvularia de la Universidad Técnica de Cotopaxi en el sector Eloy Alfaro del cantón Latacunga de la provincia de Cotopaxi durante el periodo lectivo 2011-2012 - Soria Medina, Anita Lucia (2015)
Speaking about the problem in feeding, nutrition and dietetics in children of 0-5 years old; this research aims to sensitize students who want to become teachers of young children about proper nutrition in kindergartens. Note that feeding is the main axis for the optimal development of children. That is why this research proposes workshops on feeding, nutrition and dietetics aimed at children of these ages. It is in this age where children need to strengthen their physical and mental conditions. Research also has the purpose to raise awareness among parents about the importance of this issue, since it is a sum of responsibilities to correct and amend eating habits for children.